(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article examines key areas of scientific research in speech therapy, including diagnostics, correction of speech disorders, use of technologies and interdisciplinary approaches. Particular attention is paid to modern research methods and their practical application.